The Aspergillus fumigatus UPR is variably activated across nutrient and host environments and is critical for the establishment of corneal infection. - Manali M Kamath; Jorge D Lightfoot; Emily M Adams; Ryan M Kiser; Becca L Wells; Kevin K Fuller (PLoS Pathogens, 2023)
The Aspergillus fumigatus unfolded protein response (UPR) is a two-component relay consisting of the ER-bound IreA protein, which splices and activates the mRNA of the transcription factor HacA. Spliced hacA accumulates under conditions of acute ER stress in vitro, and UPR null mutants are hypovirulent in a murine model of invasive pulmonary infection. In this report, we demonstrate that a hacA deletion mutant (ΔhacA) is furthermore avirulent in a model of fungal keratitis, a corneal infection, and an important cause of ocular morbidity and unilateral blindness worldwide. Interestingly, we demonstrate that A. fumigatus hacA is spliced in infected lung samples, but not in the cornea, suggesting the amount of ER stress experienced by the fungus varies upon the host niche. To better understand how the UPR contributes to fungal cell biology across a spectrum of ER-stress levels, we employed transcriptomics on the wild-type and ΔhacA strains in glucose minimal media (low stress), glucose minimal media with dithiothreitol (high stress), and gelatin minimal media as a proxy for the nutrient stress encountered in the cornea (mid-level stress). These data altogether reveal a unique HacA-dependent transcriptome under each condition, suggesting that HacA activity is finely-tuned and required for proper fungal adaptation in each environment. Taken together, our results indicate that the fungal UPR could serve as an important antifungal target in the setting of both invasive pulmonary and corneal infections.